The Mediating Role of Work Engagement in the Relationship between Leader-Member Exchange and Teacher Emotional Labor - Akman, Yener (Studia Psychologica, 2025)
The Leader-Member Exchange theory indicates that there are differences in the quality of the relationship between leaders and members. This means that leaders are not always equal and consistent while directing organizational sources to members. This relational differentiation influences significantly the organizational and individual outcomes at schools. We can say that the teachers’ work engagement and emotional labor approaches, especially those affecting the quality of education, are not independent from the manager-teacher exchange. Accordingly, this study aims to analyze the direct and indirect relationships among the leader-member exchange, work engagement, and emotional labor. The research data were collected from 436 teachers working in 29 public secondary schools in the central districts of Ankara province of Turkey by a random sampling technique. The relationships between the variables were analyzed with a cross-sectional research design. Structural equation modelling was used to test the proposed model. Along this line, the mediation of work engagement between the leader-member exchange and teacher emotional labor approach has been analyzed. Results have showed that leader-member exchange improves teacher emotional labor approaches by work engagement. This research contributes to studies focused on predicting the effects of leader-member exchange on teacher emotional labor.